COST EFFECTIVENESS ANALYSIS CEFTRIAXONE DAN CEFOTAXIME PASIEN OPERASI SESAR BPJS DI RSD Dr.A.DADI TJOKRODIPO : COST-EFFECTIVENESS ANALYSIS OF CEFTRIAXONE AND CEFOTAXIME IN BPJS CESAREAN SECTION PATIENTS AT RSD DR. A. DADI TJOKRODIPO - Sugianto, Anelia Arifanny; Kusniawati , Mega Ayu; Enjelina, Fina (JFL : Jurnal Farmasi Lampung, 2025)
Abstract Pharmacoeconomic analysis has several methods, one of which is cost effectiveness analysis (CEA).  Cost effectiveness analysis is a pharmacoeconomic method to select and evaluate the most appropriate program or drug among treatment options that have the same goal. This method is done to find out which of the two treatments is the most cost-effective, besides that CEA is also useful to find out which treatment is more cost-effective than the two treatment alternatives chosen, especially in cesarean section patients. This research is a type of non-experimental observational research with a retrospective descriptive research design. The sampling technique in this study uses the puRp.osive sampling technique method, sample selection is carried out based on consideration of inclusion and exclusion criteria. The sample of this study was 28 patients consisting of 15 patients who used the prophylactic antibiotic ceftriaxone and 13 patients who used the prophylactic antibiotic seflotaxis. The results of the study showed that ceftriaxone antibiotic therapy is more cost-effective, with an Average Cost-Effectiveness Ratio (ACER) of Rp89.590 per day Keywords: Cost-effectiveness analysis, cesarean section patients, ceftriaxone, cefotaxime